Socio-economic inequalities in ANC attendance among mothers who gave birth in the past 12 months in Debre Brehan town and surrounding rural areas, North East Ethiopia: a community-based survey - Gebretsadik Shibre; Wubegzier Mekonnen (BMC, 2019)
Abstract Background In Ethiopia, socio-economic inequalities in the utilization of antenatal care (ANC) have long been an obstacle to the country's effort in achieving universal coverage of the service. The study aimed to investigate socio-economic inequalities in the use of ANC services among recently-delivered women in Debre Brehan and surrounding areas, North East Ethiopia. Methods A community-based survey was carried out in Debre Brehan and surrounding areas in North East Ethiopia. Two-stage cluster sampling technique was followed to recruit study participants. Data was collected using interviewer-administered structured questionnaire from a sample of 412 mothers who gave birth in the 12 months prior to the study. The socio-economic inequalities were assessed by calculating a relative concentration index. Decomposition analysis was done to explain measured inequalities. Analysis was carried out in RStudio statistical environment using the 'decomp' package. Results The first ANC attendance has slight pro-poor concentration, with a relative concentration index of-0.128, and 95%CI -0.175, − 0.082.Socio-Economic Status (SES) of a household, educational level and occupation of a woman and her husband were the most important contributors to the measured inequality in ANC attendance. We found no SES-based inequality in the attendance of four or more ANC visits between the poor and rich. Conclusions Attendance of the first ANC visit appeared to be slightly concentrated among women in the lower end of SES. The utilization of at least four ANC visits was found to be similar among the poor and rich. Population-based interventions that target all socio-economic groups are recommended to accelerate universal coverage of these process indicators.